2020
DOI: 10.1177/1087054720923091
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish Cognitive Tempo Symptoms, But Not ADHD or Internalizing Symptoms, Are Uniquely Related to Self-Reported Mind-Wandering in Adolescents With ADHD

Abstract: Objective: The purpose of this study was to test the relation between sluggish cognitive tempo (SCT) symptoms and self-reported mind-wandering in a sample of adolescents with ADHD. Method: Adolescents ( N = 79; aged 13–17 years; 70% male) diagnosed with ADHD completed measures of SCT, ADHD, anxiety, and depression symptoms, in addition to mind-wandering. Parents also provided ratings of adolescents’ ADHD symptoms. Results: All adolescent-reported psychopathology dimensions, including ADHD, internalizing, and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In contrast to top-down executive control processes linked to ADHD-IN, greater task-unrelated thoughts have been proposed as an unique attentional feature of CDS (Barkley et al, 2022; Becker & Barkley, 2021). Specifically, CDS is more strongly associated than ADHD-IN symptoms with self-reported mind-wandering and rumination (Becker & Barkley, 2021; Becker et al, 2020; Fredrick & Becker, 2021; Fredrick, Kofler, et al, 2020). In school-aged children with high CDS, difficulties in sustained attention were significantly associated with parent ratings of social withdrawal, controlling for ADHD (Yung et al, 2021).…”
Section: Mechanisms Linking Cds To Social Withdrawalmentioning
confidence: 99%
“…In contrast to top-down executive control processes linked to ADHD-IN, greater task-unrelated thoughts have been proposed as an unique attentional feature of CDS (Barkley et al, 2022; Becker & Barkley, 2021). Specifically, CDS is more strongly associated than ADHD-IN symptoms with self-reported mind-wandering and rumination (Becker & Barkley, 2021; Becker et al, 2020; Fredrick & Becker, 2021; Fredrick, Kofler, et al, 2020). In school-aged children with high CDS, difficulties in sustained attention were significantly associated with parent ratings of social withdrawal, controlling for ADHD (Yung et al, 2021).…”
Section: Mechanisms Linking Cds To Social Withdrawalmentioning
confidence: 99%
“…Until recently, there were no data directly linking mind wandering and SCT. There are now two studies demonstrating SCT to be associated with greater mind wandering (Fredrick & Becker, 2020 ; Fredrick et al., 2020 ). These studies found the association between ADHD inattentive symptoms and mind wandering to be largely eliminated when SCT symptoms were included in the model.…”
Section: Conceptual and Empirical Overlap In Sct And Mind Wanderingmentioning
confidence: 99%
“…We spend a substantial proportion (approximately 30%–60%) of our waking hours mind wandering, or thinking about something other than what we are currently doing (Kane et al., 2007 , 2017 ; Killingsworth & Gilbert, 2010 ; Webb, Israel et al., 2021 ; see Seli et al., 2018 for the influence of response options on estimates of mind‐wandering). Although the propensity to mind‐wander may be more common among adolescents relative to children or adults (Carriere et al., 2010 ; Giambra, 2000 ; Stawarczyk, 2018 ; but see Stawarczyk et al., 2014 ), studies have only recently investigated the content, correlates and consequences of mind‐wandering in teens (e.g., Figueiredo et al., 2020 ; Fredrick & Becker, 2021 ; Mrazek et al., 2013 ; Vannucci et al., 2020 ; Webb, Israel et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given that adolescents spend a substantial proportion of their waking hours mind‐wandering (e.g., approximately 60% according to a recent ecological momentary assessment [EMA] study; Webb, Swords et al., 2021 ), research is needed to understand the extent to which these states may contribute to increases in NA. Initial research has been mixed, with some studies indicating that mind‐wandering is linked to worse affect in adolescents (Mrazek et al., 2013 ; Webb, Israel et al., 2021 ), and others failing to support this relationship (Fredrick & Becker, 2021 ). These inconsistencies may be due to prior research not distinguishing between different relevant characteristics of spontaneous thought.…”
Section: Introductionmentioning
confidence: 99%